Pengaruh kepercayaan, kepemimpinan transformasional, dan kualitas laporan keuangan terhadap keandalan pencatatan keuangan Pondok Pesantren - Kurniawati, Agustina; Mustofa, Nur Huri (Journal of Accounting and Digital Finance, 2022)
This study examines the effect of trust, transformational leadership, and the quality of financial reports on the accountability of Islamic boarding schools. This research is a type of quantitative research using a questionnaire as a data collection method. The number of samples used was 29 Kholaf Islamic boarding schools in Temanggung Regency. Data analysis used a multiple linear regression approach. The results showed that the trust variable did not affect the accountability of Islamic boarding schools. In contrast, the variables of transformational leadership and the quality of financial reports harmed the accountability of Islamic boarding schools.